Toward next‐generation engineering education: A case study of an engineering capstone project based on BIM technology in MEP systems. Issue 1 (11th August 2021) - Zhang, Jingxiao; Zhang, Zhiyue; Philbin, Simon P.; Huijser, Henk; Wang, Qian; Jin, Ruoyu
Abstract: To respond to the digital building environment and Industry 4.0 in building information modeling (BIM)‐based mechanical, electrical, and plumbing (MEP) systems this study developed a new approach to engineering capstone projects. This article reports on a case study of the development of the innovative capstone project for engineering majors, which is based on team‐based learning (TBL) combined with the 360‐degree evaluation feedback method to cultivate students' BIM competency. The data collection and analysis involves a combination of qualitative and quantitative methods, which aims to evaluate students' learning outcomes and their BIM competency. The results indicate that TBL, combined with the 360‐degree evaluation feedback in the capstone project, can be highly effective in improving graduates' BIM competency. This study discusses the interoperability of BIM software tools, problems in the process of data exchange, and provides suggestions for improving the course and BIM team collaboration. The research has identified how professional capabilities for students can be enhanced, enabled through a capstone project, and educators are able to deploy the BIM course to develop engineers that closely meet industry needs. The study provides the case for using the capstone project to improve and cultivate engineering students' BIM competency in MEP systems. This study has provided a new paradigm for applying TBL and 360‐degree evaluation feedback to engineering education.